Contested Gus Titles in Mediatized Public Culture: A Weberian Analysis of the Gus Through the Gus Miftah Controversy - Umi Ma'rufah; Tri Cahya Ramdhani (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
In contemporary Javanese Muslim society, the title Gus functions as a marker of religious distinction rooted in pesantren tradition, yet it now circulates within a public sphere that is increasingly mediatized and politicized. This study aims to explain how the title Gus works as a source of symbolic legitimacy that is produced, recognized, contested, and translated into public authority through the case of Gus Miftah, with reference to Max Weber’s typology of authority. This study employs a qualitative design based on document analysis by taking the issue of the title Gus in relation to Gus Miftah. Data were collected from secondary sources, such as scholarly works, books, journal articles, online news reports, and digital materials, which were selected purposively based on relevance, their connection to claims about authority and legitimacy, and public traceability. The analysis was conducted through repeated reading, thematic grouping, and Weberian interpretation, by comparing diverse types of sources to strengthen the credibility of the analysis. The findings show that the title Gus operates as inherited symbolic legitimacy that provides an initial basis for recognition, but its effectiveness depends on performance and circulation in public arenas. The issue of the title Gus in the case of Gus Miftah shows that when the title enters broader public spaces and political networks, legitimacy becomes open to dispute and forms a hybrid configuration of traditional prestige, charismatic visibility, and limited legal rational recognition. The implication of this study is the need to examine religious titles as mechanisms of legitimacy that are negotiated in digital and political public spheres. Gelar Gus dalam masyarakat Muslim Jawa kontemporer berfungsi sebagai penanda distingsi religius yang berakar pada tradisi pesantren, namun kini beredar dalam ruang publik yang semakin termediatisasi dan terpolitisasi. Penelitian ini bertujuan menjelaskan bagaimana gelar Gus bekerja sebagai sumber legitimasi simbolik yang diproduksi, diakui, diperdebatkan, dan diterjemahkan menjadi otoritas publik melalui kasus Gus Miftah dengan rujukan tipologi otoritas Max Weber. Penelitian ini menggunakan desain kualitatif berbasis analisis dokumen dengan mengambil isu gelar Gus pada Gus Miftah. Data dikumpulkan dari sumber sekunder, seperti karya ilmiah, buku, artikel jurnal, laporan berita daring, dan materi digital yang dipilih secara purposif berdasarkan relevansi, keterkaitan dengan klaim otoritas/legitimasi, dan keterlacakan publik. Analisis dilakukan melalui pembacaan berulang, pengelompokan tematik, serta interpretasi Weberian, dengan membandingkan beragam jenis sumber untuk memperkuat kredibilitas analisis. Hasil penelitian menunjukkan bahwa gelar Gus beroperasi sebagai legitimasi simbolik yang diwariskan dan memberi basis awal pengakuan, tetapi efektivitasnya bergantung pada performa dan sirkulasi dalam arena publik. Isu gelar 'Gus' pada Gus Miftah memperlihatkan bahwa ketika gelar memasuki ruang publik luas dan jejaring politik, legitimasi menjadi terbuka untuk dipersoalkan dan membentuk konfigurasi hibrid antara prestise tradisional, visibilitas karismatik, dan pengakuan legal-rasional yang terbatas. Implikasi penelitian ini adalah perlunya mengkaji gelar religius sebagai mekanisme legitimasi yang dinegosiasikan di ruang publik digital dan politik.